Jämbördig samverkansforskning måste få ta tid - Marie Thavenius; Martin Malmström (Educare)
In recent years, there have been several important efforts made to encourage collaborative research between teachers and researchers. Expectations for the outcomes of such research are notably high. This position paper draws on theories of collaborative research to analyse the roles, relations, and positions in a collaborative research project we participated in. The project group, comprising schoolteachers and teacher educators specializing in Swedish as a school subject, aimed to study and generate knowledge about the subject Swedish from their combined perspective. Our findings indicate that over time, the roles, relations, and positions evolved to became more equitable. This evolution led to the creation of ‘a third space’. We argue that time is crucial in collaborative research characterized by equality to make such a third space possible.